Contesting Ukrainian Nationhood: Literary Translation and the Russian-Ukrainian Conflict - Rudnytska, Nataliya (Respectus Philologicus, 2022)
The use of literary translations as an ideological weapon in the Cold War era has received considerable attention from translation scholars. However, the same tendency in today’s world remains underestimated, and research tends to be limited to political and media discourse. This paper examines the use of literary translations in the contemporary RF for contesting Ukrainian nationhood, fueling anti-Ukrainian sentiment and providing public support for the Russian military aggression against Ukraine. The research combines analysis of translated texts with examining factors that influence (non)translation and reception of works highlighting Russian-Ukrainian relations. The study focuses on translations of works by Taras Shevchenko, Nikolay Gogol and Oksana Zabuzhko and the Russian public debate concerning the role of literary translations in the Russian-Ukrainian conflict.
Keywords: literary translation; ideology; manipulation; Russian-Ukrainian conflict